DOI: 10.17077/etd.caonwmhv
|View full text |Cite
|
Sign up to set email alerts
|

Estimating standard errors of estimated variance components in generalizability theory using bootstrap procedures

Abstract: This study investigated the extent to which rules proposed by Tong and Brennan (2007) for estimating standard errors of estimated variance components held up across a variety of G theory designs, variance component structures, sample size patterns, and data types. Simulated data was generated for all combinations of conditions, and point estimates, standard error estimates, and coverage for three types of confidence intervals were calculated for each estimated variance component and relative and absolute error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…All data and analysis scripts are available for download via Open Science Framework (osf.io/bh35a). Data were pre-processed and analyzed within the R Statistical Programming Language (R Core Team, 2016 ) environment, and using the gtheory (Moore, 2016 ), psych (Revelle, 2017 ), and lme4 (Bates et al, 2015 ) packages. Graphics were created using the ggplot2 (Wickham, 2009 ) package.…”
Section: Resultsmentioning
confidence: 99%
“…All data and analysis scripts are available for download via Open Science Framework (osf.io/bh35a). Data were pre-processed and analyzed within the R Statistical Programming Language (R Core Team, 2016 ) environment, and using the gtheory (Moore, 2016 ), psych (Revelle, 2017 ), and lme4 (Bates et al, 2015 ) packages. Graphics were created using the ggplot2 (Wickham, 2009 ) package.…”
Section: Resultsmentioning
confidence: 99%
“…These measures were calculated using the “rel” package (Lo Martire, 2017) in R version 3.4.0 (R Development Core Team, 2008), and were averaged across lists. We also computed the Dependability coefficient using the “gtheory” package (Moore, 2016), both averaged across lists and based on the dataset as a whole. The ICC was calculated for the mean ratings with the parameters “two-way”, and “absolute agreement”, indicating random effects for participants and items.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Moore (2010) compared the bias and standard error of estimation of traditional methods and bootstrap method for estimating the standard error of the estimated variance components in several test design including single‐facet crossed design. Moore (2010) questioned the adequacy of the traditional method in estimating the standard errors of variance components and found that bootstrap method performed better for normal data and less for non‐normal data. In addition, Moore (2010) found the adequacy of the traditional method was more questionable with smaller sample size.…”
Section: Statistic Estimators Traditional ε̂2mentioning
confidence: 99%
“…Moore (2010) questioned the adequacy of the traditional method in estimating the standard errors of variance components and found that bootstrap method performed better for normal data and less for non‐normal data. In addition, Moore (2010) found the adequacy of the traditional method was more questionable with smaller sample size.…”
Section: Statistic Estimators Traditional ε̂2mentioning
confidence: 99%
See 1 more Smart Citation